Modular structured multilevel inverter (MSMI) for fuel cell power conditioning systems (PCS) - Ahmad Azli, Naziha; Mohamed Yatim, Abdul Halim (International Association of Science and Technology for Development, Anaheim, CA, ETATS-UNIS, 2004)
This article investigates the potentials of the modular structured multilevel inverter (MSMI) circuit topology in the development of high-power AC power supplies with specific emphasis on power-conditioning systems (PCS) for alternate sources of energy. This is due to the important role of power conditioning for utility interface in determining the future acceptance of alternate energy sources in the area of electric power systems. Fuel cell generation systems in particular are expected to see increasing practical usage due to several advantages they offer over conventional generation systems that are based on fossil fuel and nuclear power. For fuel cell generation systems to make an impact on future energy supply, they need to produce high DC-side voltages. This relates to constraints in the MSMI power devices switching frequency in order to limit its switching losses while operating in such high-voltage applications. This article proposes a control scheme that complies with the low switching frequency requirement of the MSMI power devices while fulfilling the required performance specifications of a fuel cell PCS. Both the MSMI circuit topology and its control scheme are described in detail and their performance is verified based on simulation and experimental results.